Triangle angle sum theorem and exterior angle theorem

Answer:
5.[tex]m\angle 1=47^{\circ}[/tex]
[tex]m\angle 2=137^{\circ}[/tex]
[tex]m\angle 3=31^{\circ}[/tex]
7.[tex]m\angle 1=87^{\circ}[/tex]
[tex]m\angle 2=45^{\circ}[/tex]
[tex]m\angle 3=45^{\circ}[/tex]
[tex]m\angle 4=52^{\circ}[/tex]
Step-by-step explanation:
5.[tex]\angle 1+43^{\circ}+90^{\circ}=180^{\circ}[/tex]
By triangle angle sum theorem
[tex]\angle +133^{\circ}=180^{\circ}[/tex]
Addition property of integers
[tex]\angle 1=180-133=47^{\circ}[/tex]
By using subtraction property of equality
[tex]m\angle 1=47^{\circ}[/tex]
[tex]m\angle 2=90+47=137^{\circ}[/tex]
By using exterior angle theorem
[tex]90+47+12+m\angle 3=180^{\circ}[/tex]
By using triangle angle sum theorem
[tex]149+m\angle 3=180[/tex]
Addition property of integers
[tex]m\angle 3=180-149=31^{\circ}[/tex]
Using subtraction property of equality
[tex]m\angle 3=31^{\circ}[/tex]
7.We are given that
[tex]m\angle ACD=90^{\circ}[/tex]
BC bisects angle ACD
[tex]m\angle 2=m\angle 3[/tex]
Therefore, [tex]m\angle 2=\frac{90}{2}=45^{\circ}[/tex]
[tex]m\angle 2=m\angle 3=45^{\circ}[/tex]
[tex]m\angle 1+m\angle 2+48=180^{\circ}[/tex]
By using triangle angle sum theorem
Substitute the value
[tex]45+m\angle 1+48=180[/tex]
[tex]m\angle 1+93=180[/tex]
By addition property of integers
[tex]m\angle 1=180-93=87^{\circ}[/tex]
By using subtraction property of equality
[tex]m\angle 3+m\angle 4+83=180^{\circ}[/tex]
By using triangle angle sum property
Substitute the values
[tex]45+m\angle 4+83=180[/tex]
[tex]128+m\angle 4=180[/tex]
Using addition property of integers
[tex]m\angle 4=180-128=52^{\circ}[/tex]
Using subtraction property of equality